Direct power flow method for balanced and unbalanced radial distribution systems with multi reference buses - Alwash S.F.; Ramachandaramurthy V.K. (2023)
This paper presents a direct power flow method for radial distribution systems that include different system components. When step voltage regulators are installed on strategic buses along the distribution feeders, the system will have multi reference buses. Using graph theory, a modified branch path incident matrix of multi reference buses is built and used with the current injection technique to derive a direct mathematical expression. This expression can be used to solve the load flow problem for radial distribution system with multi reference buses. The test results of IEEE 13 and 34 bus unbalanced test feeders indicate that the proposed method is efficient, robust, and accurate.